The interaction effect of personality hardiness and fear of failure to predict achievement motivation adolescents of working mother - Syarifah Farradinna; Sindy Putri Arlena (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Individuals with traits of hardiness believe that success is the result of both positive and negative life experiences. People who are highly motivated to achieve have a close relationship with intense dedication, reasonable control, and positive challenges. They are even willing to accept failure as part of the goal-setting process This study was conducted to explain the psychological characteristics of hardness and fear of failure that are predicted to determine the achievement motivation of adolescents whose mothers are employed. Participants were recruited anonymously and willingly from universities in Pekanbaru, Indonesia, Riau. After collecting and analyzing 280 questionnaires for outlier analysis, 188 were found valid for further study. Two stages of measurement were carried out; measuring was examined, and the structural model was deemed statistically significant. This study applied a quantitative methodology to the analysis of the path analysis mediation model. This study employs three measurement instruments and demographic data to address research issues. Dispositional Resilience Scale-15 (DRS-15), an action strategy to measure achievement motivation behavior personality, and the Performance Failure Appraisal Inventory (PFAI), a multidimensional assessment of cognitive-motivational-relational fear of failure, were used in this study to collect data. Path analysis from SmartPLS 3.2 was used to analyze the research data and determine the moderating and correlation values for the studied variables. This assessment indicates that fear of failure does not contribute to SMK students in Pekanbaru's toughness with success motivation. In contrast, the coefficient values for other factors indicate a positive contribution.